THE KNOCKED-OUT UNILATERAL KIDNEY! CAUSES AND PRESENTATION - Bangash, Kashif; Alam, Asaf; Amin, Mohammed; Anwar, Khursheed (Journal of Ayub Medical College Abbottabad, 2015)
Background: Due to lack of awareness and non-availability of proper medical facilities in Pakistan, patients with kidney problems tend to seek urological consultation very late when their kidney has already knocked-out. The aim of the study was to find the various presenting complaints of patients having unilateral loss of kidney function and their aetiologies. The study also targeted the patient's awareness regarding their disease. Methods: This descriptive case-series of 103 consecutive patients who were diagnosed as having less than 20% of function on DTPA Renal Scan were evaluated. The aetiology of the non-functioning kidney (NFK) was made on either imaging findings or during the exploration, and/or on histopathology if necessary. The results were analysed using SPSS 16.0. Results: The aetiology of the unilateral renal failure included those that were secondary to nephro-pelvic stones in 39.8% and ureteric stones in 14.6%. Of the other aetiologies culminating in a unilateral NFK, 7.8% of the patients had chronic pyelonephritis, 20.4 % had PUJO and 5.8% were Genito-urinary Tuberculosis; 3.9% had VUR and were found incidentally, 3.9% developed non-functioning kidney iatrogenically. About 39.8% of the patients knew about their primary disease causing destruction of renal function since long. The remaining 60.2% were unaware that they had developed NFK already when they presented. Conclusion: Proper education through awareness program both for the public and general practitioners can detect early threats to the kidney and hence decrease the loss of a kidney. This will also decrease the number of nephrectomies carried out for the benign conditions.